Efficiency in Islamic Rural Banks: What Factors Make Things Worse? - Multazam Mansyur Addury; Amar Maruf; Yuniar Lestari (Journal of Finance and Islamic Banking, 2025)
This study is designed to conduct an analysis of the efficiency of Islamic Rural Banks IBRs within the Indonesian context and to examine the significant variables that influence efficiency both in Java and outside of Java. This study uses Two-Stage (DEA) Data Envelopment Analysis technique on 83 IBRs in Indonesia with the period used is 2011 - 2023. The results showed that overall, the efficiency of IBRs in Indonesia is relatively low, where only a small portion is considered efficient. The majority of IBRs fall into the Decreasing Returns to Scale (DRS) category, where input expansion leads to a relatively smaller increase in output. The Covid-19 pandemic has also been shown to have a negative and significant effect on the efficiency of IBRs, especially outside Java, while the effect is not significant for IBRs in Java. Return On Assets (ROA) and total assets consistently having a positive impact in the Java region and Indonesia as a whole. This study makes an important contribution to understanding the operational efficiency of IBRs in Indonesia and provides policy recommendations that can strengthen the competitiveness of IBRs, particularly by optimizing asset management, improving operational resilience in areas outside Java, and leveraging regional economic growth.